Impact of C‐terminal amino acid composition on protein expression in bacteria. Issue 5 (25th May 2020) - Weber, Marc; Burgos, Raul; Yus, Eva; Yang, Jae‐Seong; Lluch‐Senar, Maria; Serrano, Luis
Abstract: The C‐terminal sequence of a protein is involved in processes such as efficiency of translation termination and protein degradation. However, the general relationship between features of this C‐terminal sequence and levels of protein expression remains unknown. Here, we identified C‐terminal amino acid biases that are ubiquitous across the bacterial taxonomy (1, 582 genomes). We showed that the frequency is higher for positively charged amino acids (lysine, arginine), while hydrophobic amino acids and threonine are lower. We then studied the impact of C‐terminal composition on protein levels in a library of Mycoplasma pneumoniae mutants, covering all possible combinations of the two last codons. We found that charged and polar residues, in particular lysine, led to higher expression, while hydrophobic and aromatic residues led to lower expression, with a difference in protein levels up to fourfold. We further showed that modulation of protein degradation rate could be one of the main mechanisms driving these differences. Our results demonstrate that the identity of the last amino acids has a strong influence on protein expression levels. Synopsis: Large‐scale genomics analyses combined with high‐throughput experimental assays reveal that the C‐terminal amino acid composition has a strong influence on protein expression levels in bacteria. C‐terminal amino acid biases are ubiquitous across bacterial taxonomy: positively charged residues (lysine, arginine) are enriched at the last position, while hydrophobic amino acids and threonine are depleted. High‐throughput expression assays using a reporter gene library showed that protein expression varies up to 4‐fold, with C‐terminal positively and negatively charged residues increasing expression, and hydrophobic residues decreasing expression. Modulation of protein degradation rate due to the identity of the C‐terminal residue could explain ˜ 85% of the variation in protein expression. These results are relevant for the optimization of heterologous protein sequences, where the choice of C‐terminal residues could lead to increased expression levels. Abstract : Large‐scale genomics analyses combined with high‐throughput experimental assays reveal that the C‐terminal amino acid composition has a strong influence on protein expression levels in bacteria.